Nilai Tolong-menolong dalam Tradisi Pengajian Parkahanggian Marga di Desa Pidoli Lombang Kabupaten Mandailing Natal (Kajian Living al-Qur’an) - Azhar Azhar Nasution; Rusydi AM; Widia Fithri (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2021)
Pengajain Parkahanggian in which it has a strong mutual help value. The Parkahanggian Marga recitation is a religious activity that reads the verses of the Qur'an in it and brings the verses of the Qur'an to life by reading and practicing it. This research is a qualitative field research, using descriptive analysis method, data collection using observation, interview and documentation techniques. Based on this research, the authors found that the tradition of the Parkahanggian recitation in Pidoli Lombang village has been going on for a long time, some findings indicate that this recitation came from Shaykh Ma'sum who lived in the village, some said that this recitation was started by the parkahanggian clan of Borotan. Some of the motivations for the community to conduct this recitation are to help each other, preserve traditions, do good deeds and send rewards to those who have gone before, and establish friendship. The first phase of the Parkahanggian recitation procession was reading verses from the Qur'an such as al-Fatihah, al-Ikhlas, al-Falaq an-Nas, al-Baqarah, tahlil and prayer, the second phase was markobar (speaking), the last phase was marpio (calling). name), this recitation was held on Friday night after the Isa prayer, the men involved. This recitation is a place for mutual help between brothers and sisters in the same family, in this tradition there are also Qur'anic values ​​that are understood and practiced. Its implementation involves all heads of households. The value of mutual assistance is very thick in this Parkahanggian recitation both in joy and sorrow. Among the forms of mutual assistance are assistance in the form of energy, money and thoughts that are donated and given when there are parties and misfortunes, kahanggi will be very helpful. All of that departs from people's understanding of the teachings of the Qur'an to do good.